2014
DOI: 10.1105/tpc.114.123968
|View full text |Cite
|
Sign up to set email alerts
|

POLYGALACTURONASE INVOLVED IN EXPANSION1 Functions in Cell Elongation and Flower Development in Arabidopsis

Abstract: Pectins are acidic carbohydrates that comprise a significant fraction of the primary walls of eudicotyledonous plant cells. They influence wall porosity and extensibility, thus controlling cell and organ growth during plant development. The regulated degradation of pectins is required for many cell separation events in plants, but the role of pectin degradation in cell expansion is poorly defined. Using an activation tag screen designed to isolate genes involved in wall expansion, we identified a gene encoding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
205
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 157 publications
(213 citation statements)
references
References 76 publications
6
205
0
2
Order By: Relevance
“…A recent study that combined extensometry with atomic force microscopy and different forms of cell wall strain showed that both cellulose microfibrils and matrix polymers, predominantly pectins, bear the tensile load of elastically stretched onion walls (Zhang et al, 2017). This confirms the mechanical significance of the matrix at the molecular scale and adds impetus to recent interest in the state of pectins in growing cell walls and the need for better models of cell wall mechanics (Peaucelle et al, 2012;Xiao et al, 2014;Levesque-Tremblay et al, 2015).…”
Section: Discussionmentioning
confidence: 58%
“…A recent study that combined extensometry with atomic force microscopy and different forms of cell wall strain showed that both cellulose microfibrils and matrix polymers, predominantly pectins, bear the tensile load of elastically stretched onion walls (Zhang et al, 2017). This confirms the mechanical significance of the matrix at the molecular scale and adds impetus to recent interest in the state of pectins in growing cell walls and the need for better models of cell wall mechanics (Peaucelle et al, 2012;Xiao et al, 2014;Levesque-Tremblay et al, 2015).…”
Section: Discussionmentioning
confidence: 58%
“…For example, pectin demethylesterification triggers an increase in wall elasticity during shoot meristem initiation (Peaucelle et al, 2011). In two recent studies, we reported that tissue expansion is promoted when pectin molecular mass is reduced (Xiao et al, , 2014, suggesting a link between pectin size and wall stiffness in growing vegetative tissues.…”
Section: Introductionmentioning
confidence: 99%
“…HG, the predominant form of pectin in primary cell walls of Arabidopsis thaliana (Zablackis et al, 1995), is synthesized in a highly methylesterified form and can be demethylesterified upon delivery to the cell wall by pectin methylesterases (PMEs), generating negatively charged carboxyl groups on its GalA residues. Pectin demethylesterification can occur in continuous blocks or at random GalA residues, resulting in either wall stiffening via the formation of Ca 2+ -cross-linked HG networks (Vincken et al, 2003) or wall loosening by means of pectin-degrading enzymes (Xiao et al, 2014). Pectin methylesterification status and molecular mass can have profound impacts on wall mechanics, affecting both cellular growth and tissue growth (Braybrook and Jönsson, 2016;Hocq et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…While the egg-box model predicts that PME activity increases the stiffness of the pectic matrix, the atomic force microscopy experiments found that demethylesterification of HG promoted wall loosening and was a prerequisite for organ initiation (Peaucelle et al, 2011). Therefore, unesterified HG in growing cells is likely targeted by pectincleaving enzymes such as the recently identified polygalacturonanses involved in cell expansion (PGX1, PGX2, and PGX3), which are required for the development of multiple Arabidopsis organs (Xiao et al, 2014Rui et al, 2017).…”
Section: Monitoring Pectic Structuresmentioning
confidence: 99%